2006
DOI: 10.2105/ajph.2005.068262
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Naturally Occurring Retirement Communities: A Low-Cost Approach to Facilitating Healthy Aging

Abstract: Naturally occurring retirement communities (NORCs) are broadly defined as communities where individuals either remain or move when they retire. Using the determinants of health model as a base, we hypothesize that some environmental determinants have a different impact on people at different ages. Health benefits to living within NORCs have been observed and likely vary depending upon where the specific NORC exists on the NORC to healthy-NORC spectrum. Some NORC environments are healthier than others for senio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…Multi-stakeholder collaborations can enable different groups of people with a common goal to work together. The literature suggested that these collaborations included activities that are targeted specifically to those approaching old age or older persons themselves (Alpay et al, 2004;Hanson & Emlet, 2006;Masotti, Fick, Johnson-Masotti, & Macleod, 2006;Paganini-Hill, 2013;Simpson, 2010;Tam, 2013). For example, the Healthy Ageing in Canada report illustrates the importance of national governments working with regional governments, research institutions and other organisations to address ageing issues (PHAC, 2006).…”
Section: Intersectoral Collaboration and Political Commitmentmentioning
confidence: 99%
“…Multi-stakeholder collaborations can enable different groups of people with a common goal to work together. The literature suggested that these collaborations included activities that are targeted specifically to those approaching old age or older persons themselves (Alpay et al, 2004;Hanson & Emlet, 2006;Masotti, Fick, Johnson-Masotti, & Macleod, 2006;Paganini-Hill, 2013;Simpson, 2010;Tam, 2013). For example, the Healthy Ageing in Canada report illustrates the importance of national governments working with regional governments, research institutions and other organisations to address ageing issues (PHAC, 2006).…”
Section: Intersectoral Collaboration and Political Commitmentmentioning
confidence: 99%
“…The unifying framework would facilitate access to both medical and long term supports and services. The continuum of choices would range from more traditional congregate settings to community based options like "naturally occurring retirement communities" (Masotti, Fick, Johnson-Masotti, & MacLeod, 2006) and "Villages," cooperativetype models in which neighbors band together to procure services (Butler & Diaz, 2015;Greenfield, Oberlink, Scharlach, Neal, & Stafford, 2015).…”
Section: Housing and Bringing It All Homementioning
confidence: 99%
“…Americans are increasingly choosing to age in place in their homes and communities to be near family and friends, and the concept of aging itself is changing for many adults, including Boomers and those age 65 and older (Fessenden, 2006;Gross, 2007;Masotti, Fick, Johnson-Masotti, & MacLeod, 2006;Moody, 2006). Suburbia is changing as well.…”
Section: Demographic and Health Care Challenges And Occupational Thermentioning
confidence: 99%